Intoxicated Individuals Responsible for Breaches of the Peace (Archives of Criminology, 1974)
This work discusses the results of investigations conducted by the Polish Academy of Sciences Department of Criminology, concentrating contraventions (petty misdemeanours) committed in Warsaw by “disturbance of public peace or by giving rise in a state of intoxication to indignation in a public place or place of work”. Such contraventions were covered by Art. 27 of the 1954 Act on Fighting Alcoholism, which provides for three months of imprisonment or a fine of 4,500 zlotys. As from 1972, the new Contravention Code makes the following provisions for such offences (Art. 51).Para. 1. Whoever disturbs peace, public order or night rest with shouting, noise, alarm signals or other disorder or gives rise to public indignation is liable to two months imprisonment, a fine up to 3,000 zlotys, or a reprimand.Para. 2. If the act designated in para. 1 is of the nature of hooliganism or if the offender committed it while intoxicated he is liable to three months imprisonment, to limitation of personal freedom, or to a fine (up to 5,000 zlotys).The average number of those annually convicted in Poland of disturbing the peace while intoxicated amounted between 1970-1972 to ca. 167,930, and between 1965-1967 to ca. 122,900.The average annual number of individuals convicted in Warsaw between 1970-1972 amounted to ca. 14,730, and between 1965 and 1967 ‒ to 11,800.Investigations were conducted in 5 out of 7 Penal Administrative Commissions (bodies of citizens empowered to deal with contraventions), under the auspices of the Boards of People’s Councils and involved some 900 men, convicted in 1967 of the contraventions indicated above. Data concerning all of them were collected from official records of convictions and prison terms up to the end of 1972. A random sample of 300 (out of those 900) were investigated as regards further sentences passed by Penal Administrative Commissions during the years 1967-1972 for new cases of breach of the peace while intoxicated, information as to time spent in detoxication centre (where drunks are held until sober), and police records of arrest in public places in a state of intoxication of those investigated.Data obtained concerning the number of cases tried by Penal Administrative Commissions cannot be considered as complete.The age of individuals who committed relevant offences in 1967 was as follows:17-20 ‒ 10.8%    (96),            35-39 ‒ 14.6%            (127),21-24 ‒ 11.2%  (100),             40-44 ‒ 10.3%           (90),25-29 ‒ 17.8%  (158),             45-49 ‒ 6.5%  (58),30-34 ‒ 19.5%  (175),            50 and over ‒ 9.3% (83).            Note that the group from 40 years old and above is more numerous (26%) than the group aged 17-24 (22%).The average age of those investigated in 1967 was 33 years, the median ‒ 32 years.The average age of those investigated in 1972 was 38 and the median ‒ 37.During the five years between 1967 and 1972 out of the 300 men of the random sample, 59% were only once charged with disturbing public order while intoxicated, 17% ‒ twice, 9% ‒ 3 times and 16% ‒ 4 times or more.But taking into account additional information about detainments in detoxication centre, arrests by the police in public places while intoxicated, and also criminal records, it appears that during the cource of five years only 20% of those investigated, who were only once charged before a Penal Administrative Commission for disturbing public order, did not, while intoxicated, get into such trouble as involved police intervention.Note that 34% of those tried once by the Penal Administrative Commission has been convicted by the court, and as many as 71% of those tried at least twice. Conviction by regular courts of those investigated will be discussed briefly at the end of this summary.Taking into account, in addition to, arraignments before a Penal Administrative Commission, only detainment in detoxication centre and arrest by the police for being intoxicated, the situation is as follows:‒ among those arraigned before a Penal Administrative Commission only once for disturbing public order, arising out of intoxication, further cases of police intervention on grounds of insobriety were recorded during the course of five years as concerning 53%;‒ among those twice convicted by a Penal Administrative Commission, police intervention more than twice was recorded as regards 81% of those investigated;‒ among those convicted three times by a Penal Administrative Commission, police intervention more often than three times was recorded as regards 96%, and among those convicted four times and more by Penal Administrative Commission, there were none with less than 5 cases of police intervention.Police intervention at least as many as six times was depending on the number of convictions for contravention due to intoxication (1, 2, 3 and 4 and more convictions by the Penal Administrative Commission) as follows: 12% ‒44% ‒69% and 92%.Police intervention at least as many as ten times necessitated by intoxication ‒ 5% ‒ 10% ‒ 19% and 50%.4l% kept altogether out of a detoxication centre during the fiveyear period, 20% were there once, 9% ‒ twice, 15% ‒3-4 times and 15% ‒ 5 times or more.Among those investigated who kept altogether out of a detoxication centre was a significantly larger percentage of people with only one case of arraignment before a Penal Administrative Commission. Among those appearing on the records of detoxication centre there were also some who had in addition been arrested by the police for intoxication (without having been sent to detoxication centres).Note that, together with the increase in the number of convictions by a Penal Administrative Commission, there is also a marked growth in the percentage of those conveyed to detoxication centre ‒ from 50% to 73%.Taking into account data on offenders tried by courts from the time they were 17 years old till 1972, when their average age amounted to 37 years, it was found, that 50% of those who disturbed public order while intoxicated, had not yet been convicted by courts, 19% had been convicted once, 19% ‒ 2-3 times and 12% ‒ at least 4 times,There is a significant difference between those not convicted and those convicted by a court, depending on the number of their arraignment in a Penal Administrative Commission. While 75% of those investigated who had not been convicted by a court had been tried by a Penal Administrative Commission only once, this applied only to 40% of those who had been convicted by a court; only 5% of those not convicted and 27% of those convicted by a court had been arraigned before a Penal Administrative Commission 4 times or more.Together with the number of triars by penal Administrative Commission there is a decrease also in the percentage of persons not convicted by a court, while the percentage of individuals convicted once increases from 16 to 24, of those convicted 2-3 times ‒ from 13 to 28 and of those convicted 4 times and more ‒ from 5 to 27.Examination of the age at which those investigated were first convicted by a court, revealed that in the group of those convicted 1-3 times by a court, 25%  had been sentenced for the first time at the age of 17-20 years, 25% at the age of 21-24. Of those convicted 4 times or more, 38% had been sentenced for the first time when 17-20 years old and 26% at the age of 21-24. Thus, there were more recidivists with multiple convictions among those arraigned for the first time when still under 21.As many as 38% of those convicted less than 4 times and 19% of those convicted 4 times or more were arraigned for the first time after the age of 30.Note that only 18% of delinquents between 17 and 20 had been charged in the Juvenile Court while under 17.Although as regards the group of recidivists convicted 4 times and more it was found that there had been convictions at an earlier age than was the case with those convicted 1-3 times, nevertheless this initiation was markedly later than was the case with the typical multiple recidivists who were previously investigated by the Polish Academy of Sciences Department of Criminology. Among those recidivists as many as 67% had been previously convicted when under 21; among those who disturbed public order while intoxicated and were convicted by court, the corresponding percentage is 37%.The structure of offences of the individuals investigated, is highly characteristic of people who systematically consume alcohol to excess. Among the offences for which those investigated were convicted by courts less than 4 times, only 24% were qualified as offences against property, while as many as 46% were offences involving aggression (as a rule physical aggression) ‒ with a predominance of minor assaults without causing any bodily harm and slight bodily injuries or assaults on policemen, as a rule committed under the influence of alcohol.Even among offences of which were convicted recidivists who had already previously been sentenced at least four times, not more than 33% stole, while as many as 51% committed offences involving aggression (of the kind of those already referred to).Offences against the person committed by all those investigated were usually (80%) minor assaults and slight bodily injuries; not more than 13% lead to serious crimes of this type.In analysing data on offences committed by those investigated it should be borne in mind that 52.5% of the total of those responsible for breaches of the peace while under the influence of alcohol had not been previously convicted by a court and approximately 20% have been convicted only once. * The research here discussed, covering a five-year period after a hearing in 1967 before a Penal Adrninistrative Commission and serving as a starting point for further studies, revealed trends of some practical importance:‒ together with the growing number of trials of breach of the peace while under the influence of alcohol, there is an increase in the numer of individuals investigated who were brought to detoxication centres, in the frequency of such occasions, and in other interventions by the police; moreover records show a growing percentage of those convicted by courts and of recidivists, convicted four times or more;– the percentage of individuals investigated who have to be taken to the detoxication centres shows an increase from 50% in the case of those only once arraigned before a Penal Administrative Commission to 71% with the case of those arraigned twice, and 73% of those charged at least three times in the Commission;– as from the second trial of an individual before a Penal Administrative Commission an intensified deterioration is to be observed in behaviour as a result of excessive consumption of alcohol; this justifies classifying such individuals as excessive drinkers, in many cases already on the verge of alcoholism or even already alcoholics.